Management of Posttraumatic Enophthalmos Including Complex Secondary Deficits - Gengler, Isabelle; Hsieh, Tsung-yen (Facial Plastic Surgery, 2022)
Posttraumatic enophthalmos (PE) arises when the ocular globe is displaced posteriorly and inferiorly in the orbital cavity due to a mismatch in orbital volume and orbital content. This most commonly happens after orbital fractures. The resulting disruptions to aesthetic form and ocular functions often necessitate surgical correction for reconstruction and restoration. The purpose of surgical management of PE is to reconstruct orbital shape and volume as well as to restore any herniated orbital content. This can be particularly challenging in cases involving large defects that require complex orbital reconstruction. Recent advancements in computer-aided surgery have introduced innovative and important tools to assist surgeons with these difficult cases. The ability to create customized, patient-specific implants can facilitate reconstruction involving complicated anatomy. Additionally, intraoperative imaging and intraoperative navigation can serve as useful guides for surgeons to more accurately place implants, especially in cases with limited visualization, in order to achieve optimal outcomes.
Keywords: enophthalmos; computer-aided surgery; intraoperative navigation; intraoperative imaging; orbital fractures